Box-Behnken Design Assisted Optimization and Standardization of Chromatographic Methodology for Quality Assessment of Metformin: Analytical Quality by Design Avenue - Suryawanshi, Shailendra S; Palled, Mahesh S (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Metformin (MET) is an oral antidiabetic agent falls chemically under the category of biguanides and it is effectively utilized in the management of type 2 diabetes mellitus. It is marketed in the tablet dosage form and hence quality control and assessment of MET is very much essential and important. Objectives: The objectives of present research investigation are to implement the Box-Behnken Design (BBD) in the optimization and validation of Reverse Phase-High Performance Liquid Chromatographic (RP-HPLC) method for the quality assessment of MET and also to systematically apply the Analytical Quality by Design (AQbD) Approach. Materials and Methods: In methodology BBD was employed to identify and optimize the critical method aspects for augmenting the performance of proposed methodology. The optimum chromatographic elution was performed on Agilent C18 (5μm, 250 × 4.6 mm i.d.) column employing methanol and 0.1% ortho phosphoric acid in water with pH 2.8 in the proportions of 4:96 v/v as solvent system. The elution was carried out at 0.7 mL/min flow of mobile phase and identification at 231 nm using UV detector. The BBD driven optimized method was standardized as per guidelines of International Council for Harmonisation Q2 (R1) in terms of validating method parameters such as specificity, linearity, detection and quantitation limit, precision, robustness, ruggedness and accuracy. Results: The method was linear in the concentration of 5-25μg/ml with R2 = 0.999. The detection and quantitation limit were obtained at concentration of 0.30 and 0.93 μg /ml. The values of precision, robustness, and ruggedness parameters were found to be well within the required limit of acceptance with deviation of relative standard < 2%. The accuracy of MET was observed 99.22% to 100.25% at three different recovery experiments. At the end the proposed design of experiment (DoE) oriented methodology successfully applied for quantification of MET. Conclusion: The BBD and AQbD approaches are highly useful for the quality assessment of MET in bulk and its marketed tablet dosage forms
Keywords: Analytical Quality by Design; Box–Behnken Design; Chromatography; Metformin; Standardization